Epidermoid Cyst in the Lateral Eyebrow (Frontozygomatic Suture) Region and Review of Literature - Deepthi, Shetty; Prashanth, Shetty (Journal of Health and Allied Sciences NU, 2017)
Epidermoid cysts are non odontogenic, developmental pathologies occurring in the head and neck region with an incidence ranging from 1.6% to 6.9%. Ambiguity about their exact pathogenesis exists and several theories have been postulated. Histologically they have cystic capsule lined by squamous epithelium without skin appendages. We have described a case of an epidermoid cyst in the lateral eyebrow region and its effective management with a brief review of literature.
Keywords: Epidermoid cyst; frontozygomatic suture